Associations between ultra-processed food consumption and duration of exercise with psychological symptoms in Chinese adolescents: a nationwide cross-sectional survey - Zheng, Wei; Xiong, Jianping; Huang, Bo; Kong, Qingtao (Frontiers in Nutrition, 2025)
BackgroundGlobally, ultra-processed food (UPF) consumption among adolescents is increasing, and the duration of exercise is decreasing, which has a serious negative impact on adolescents’ physical and mental health. In addition, the prevalence of psychological symptoms among Chinese adolescents is also increasing, which affects adolescents’ lives and academic performance. However, the association between UPF consumption, duration of exercise, and psychological symptoms among Chinese adolescents is still unclear. This study aims to analyze the association between UPF consumption, exercise duration, and psychological symptoms in Chinese adolescents.MethodsThis study used cross-sectional data from 2023 on 14,445 adolescents aged 13–18 years in five regions of China. In this study, a self-assessment questionnaire was used to assess UPF consumption and duration of exercise, and the Brief Instrument on Psychological Health of Youths (BIOPHY) questionnaire was used to assess adolescents’ psychological symptoms. In addition, factors affecting participants’ psychological symptoms were evaluated for height, weight, grip strength, standing long jump, father’s education, mother’s education, commuting style, and sleep duration. The t-test, chi-square test, binary logistic regression analysis, and ordered logistic regression analysis in a generalized linear model were used to assess the existence of associations between UPF consumption, duration of exercise with psychological symptoms.ResultsThe prevalence rates of emotional problems, behavioral problems, and social adjustment difficulties among Chinese adolescents were 28.2, 28.0, and 17.6%, respectively; and the prevalence rate of psychological symptoms among Chinese adolescents was 22.0%. Adolescents with lower exercise durations (<30 min/day) and higher UPF consumption (>6 times/week) were 1.54 times more likely to experience psychological symptoms compared to their peers with healthier behaviors.ConclusionUltra-processed food consumption and duration of exercise were associated with psychological symptoms in Chinese adolescents. The higher the UPF consumption and the shorter the duration of exercise, the higher the prevalence of psychological symptoms. These findings highlight the need for public health strategies focusing on reducing UPF consumption and promoting regular exercise to mitigate psychological symptoms among adolescents.